High-Dose Sublesional Bevacizumab (Avastin) for Pediatric Recurrent Respiratory Papillomatosis. (March 2014) - Sidell, Douglas R.; Nassar, Michel; Cotton, Robin T.; Zeitels, Steven M.; de Alarcon, Alessandro
Objectives: We review and report the use of high-dose bevacizumab for the treatment of recurrent respiratory papillomatosis (RRP) in pediatric patients. Methods: We included all patients with pediatric-onset RRP who underwent bevacizumab (25 mg/mL) injections by a single practitioner. A series of 5 consecutive subepithelial injections were administered at 4- to 6-week intervals with concomitant 532 nm KTP laser ablation. The lesions were staged according to the Derkay staging system. The outcomes included pretreatment and posttreatment Derkay scores, the time interval between procedures, and voice outcomes. The demographic data extracted included sex, age at diagnosis, and current age. Results: Nine patients were included in this study, with 1 patient lost to follow-up; their median age was 8 years (range, 3 to 21 years). The mean bevacizumab dose was 14.25 mg (range, 5 to 45 mg). There was a median Derkay score of 11.5 (range, 4 to 23) at the time of diagnosis and a median 58% improvement following therapy. All patients demonstrated an increased time interval between injections, for a median improvement of 2.05× (range, 1.6× to 3.25×). Conclusions: Evidence exists in support of vascular endothelial growth factor as an important factor in the development of RRP. Although some variability in response is demonstrated by this study, high-dose bevacizumab appears to yield promising results for pediatric patients with RRP.